Entrepreneurial Skills to Be Successful in the Global and Digital World: Proposal for a Frame of Reference for Entrepreneurial Education - Jacinto Jardim (MDPI AG, 2021)
For most professionals to succeed in the current job market, they need some entrepreneurial skills (ES). This study aimed to describe and systematize these skills, considering the current globalization and digital transformation phenomena. The documental analysis and the critical reflection on the collected data allowed us to identify the socio-economic and socio-cultural reasons for the relevance of this problem. Consequently, to elaborate a frame of reference intended to be adequate to the needs of the professionals of the current global and digital era. The results pointed to a tripartite ES model-to be open to novelty, to create solutions to emerging problems, and to communicate effectively-which integrates the following skills: Creativity and innovation, the spirit of initiative, self-efficacy and resilience, strategic planning, and evaluation, resolution of problems and decision-making, transformational leadership, clear and visual communication, teamwork and networking, and digital communication. In the continuation of this study, an ES scale will be created and validated according to this model, which will make it possible to measure the degree of development of these competencies.